High BTLA Expression Likely Contributes to Contraction of the Regulatory T Cell Subset in Lupus Disease - Aubergeon, Lucie; Sawaf, Matthieu; Felten, Renaud; Gottenberg, Jacques-Eric; Dumortier, Hélène; Monneaux, Fanny (Frontiers in Immunology, 2021)
B and T lymphocyte attenuator (BTLA) is a co-inhibitory receptor that is expressed by lymphoid cells and regulates the immune response. Consistent with an inhibitory role for BTLA, the disease is exacerbated in BTLA-deficient lupus mice. We recently demonstrated that the BTLA pathway is altered in CD4+ T cells from lupus patients. In the present work, we aimed at delineating the expression pattern of BTLA on CD4+ T cell subsets suspected to play a key role in lupus pathogenesis, such as circulating follicular helper T cells (cTFH) and regulatory T cells (Tregs). We did not detect significant ex vivo variations of BTLA expression on total CD4+ T cells (naive and memory), cTFH or TFH subsets between lupus patients and healthy controls. However, we interestingly observed that BTLA expression is significantly increased on activated Tregs, but not resting Tregs, from lupus patients, especially those displaying an active disease. Moreover, it correlates with the diminution of the Tregs frequency observed in these patients. We also showed that both BTLA mRNA and protein expression remain low after TCR stimulation of activated Tregs sorted from healthy donors and evidenced a similar dynamic of BTLA and HVEM expression profile by human Tregs and effector CD4+ T cells upon T cell activation than the one previously described in mice. Finally, we observed that the HVEM/BTLA ratio is significantly lower in Tregs from lupus patients compared to healthy controls, whereas ex vivo effector CD4+ T cells express higher BTLA levels. Our data suggest that an altered expression of BTLA and HVEM could be involved in an impaired regulation of autoreactive T cells in lupus. These results provide a better understanding of the BTLA involvement in lupus pathogenesis and confirm that BTLA should be considered as an interesting target for the development of new therapeutic strategies.